Effects of Worsening Renal Function and Changes in Blood Urea Nitrogen Level During Hospitalization on Clinical Outcome in Patients with Acute Decompensated Heart Failure - Masaru Hiki; Takatoshi Kasai; Akihiro Sato; Sayaki Ishiwata; Shoichiro Yatsu; Hiroki Matsumoto; Jun Shitara; Megumi Shimizu; Azusa Murata; Takao Kato; Shoko Suda; Hiroshi Iwata; et al. (Biomedicines)
Background/Objectives: Worsening renal function (WRF) during hospitalization for acute decompensated heart failure (ADHF) is associated with poor clinical outcomes. Data on the impact of WRF on clinical outcomes, considering blood urea nitrogen (BUN) level and its changes in patients with ADHF, are scarce. This study aimed to investigate the effects of BUN and its changes during hospitalization on the relationship between WRF during hospitalization and post-discharge clinical outcomes in patients with ADHF. Methods: A total of 509 patients with ADHF, hospitalized between 2007 and 2011, were included. WRF was defined as an absolute increase in serum creatinine level of >0.3 mg/dL, with a >25% increase during hospitalization. The risk of WRF for post-discharge clinical events, including death and rehospitalization, considering BUN levels, was assessed using three multivariable Cox regression models. Results: WRF was observed in 55 (10.8%) patients. The cumulative event-free survival was significantly worse in patients with WRF (p = 0.039). In Model 1 (excluding BUN changes), WRF was associated with a greater risk of post-discharge clinical events. In Model 2, which included both WRF and BUN changes, WRF was not a significant predictor. In Model 3, patients were subdivided according to WRF or BUN increase, and the subgroups were included instead of isolated WRF and BUN changes; only WRF with increased BUN level was associated with an increased risk of post-discharge clinical events. Conclusions: In patients with ADHF, WRF was associated with poor post-discharge clinical outcomes when accompanied by increased BUN levels during hospitalization.